Comparison of Rescue and Relief Activities Within 72 Hours of the Atomic Bombings in Hiroshima and Nagasaki - Matsunari, Yuko; Yoshimoto, Nao (Prehospital and Disaster Medicine, 2013)
To clarify the factors and reasons for the differences in the outcomes of rescue and relief efforts in Hiroshima and Nagasaki, mainly focusing on the numbers of rescue/relief staffs and casualties in the period within 72 hours of the atomic bombings in August 1945. By retrieving the data and information from the records and reports concerning the disasters in the two cities, together with other publications as to the damages by the atomic bombings and subsequent rescue-relief activities, and restoration activities. It seems that there was less damage in Nagasaki, where a stronger atomic bomb was used than in Hiroshima. There were crucial geographic factors that led to the different effects in terms of the numbers of victims; however, systematic organization and mobilization of rescue and relief staffs, maintenance of functional transportation, and advanced medical knowledge and public warning with regard to disaster all may have contributed to a lower death toll and increase in survivors in Nagasaki.